The future of the Autonomous Emergency Braking for Powered-Two-Wheelers: field testing end-users' acceptability in realistic riding manoeuvres. Issue 1 (February 2021) - Marra, M; Lucci, C; Huertas-Leyva, P; Baldanzini, N; Pierini, M; Savino, G
Abstract: Motorcycle Autonomous Emergency Braking system (MAEB), is a technology that introduces also on Powered-Two-Wheelers (PTWs) the autonomous braking, which is able to apply autonomously a braking force to reduce impact speed in emergency situations. This system was shown to be possibly effective in reducing numbers of deaths and serious injuries resulting from motorcycle crashes. However, its safe applicability on standard vehicles and the acceptability among end-users has still to be proven. The goal of the study presented in this paper is to assess the acceptability and the controllability of automatic braking events deployed in realistic riding manoeuvres. Field tests were conducted involving 55 common riders as participants on three test vehicles: a naked motorcycle, a sport touring motorcycle and three-wheels scooter. The automatic braking was tested in four riding manoeuvres (straight-lane, lane-change, slalom, and curve) deployed remotely by an investigator at a travelling speed of 35-50 km/h. The system was tested with the higher levels of interventions tested so far by common users and more than 1100 interventions were recorded. The results of this study will allow having a new understanding on the limits of MAEB system.